The Effect of Competence, Motivation, and Job Satisfaction on Employee Performance Pt. Media Bengkulu Online Success - Maharani, Nana; Soleh, Ahmad; Febliansa, M Rahman (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of competence, motivation and job satisfaction on employee performance at PT Media Bengkulu Online Sukse.nThe type of research used in this study is associative research with a quantitative approach with a research method that utilizes numbers, starting from data collection to interpretation and presentation of results. The number of samples used in this study was 30 people. The data collection techniques in this study were observation and questionnaires measured using SPSS Software. The data analysis techniques used were multiple linear regression, coefficient of determination, and hypothesis testing. The results showed that there was an effect of competence (X1) on employee performance (Y) at PT. Media Bengkulu Online Sukses with a sig value of 0.000 <0.05 and tcount> ttable (6.760>0.135) from the significance value obtained that variable X had an effect on employee performance (Y). from the significance value obtained that the motivation variable (X2) has an effect on employee performance (Y) with a sig value of 0.005 <0.05 and tcount> ttable (8.427>0.135). There is an effect of job satisfaction (X3) on employee performance (Y) PT. Media Bengkulu Online Sukses with a sig value of 0.004 <0.05 and tcount> ttable (6.909>0.135) variable X3 has an effect on employee performance (Y). So it can be concluded that together the independent variables have a significant effect on the dependent variable.